Stigmaeus lorestaniensis, a new species of the genus Stigmaeus (Acari: Stigmaeidae) from Southwest of Iran - Mohammad Ahmad-Hosseini; Shahriar Jafari (Persian Journal of Acarology)
A new species of the genus Stigmaeus Koch, 1836 (Acari: Trombidiformes: Stigmaeidae), S. lorestaniensis sp. nov. is described and illustrated. This new species was collected from soil and litter under apricot tree, Prunus armeniaca L. (Rosaceae) in Lorestan province, southwest Iran.